DETERMINING THE PRIORITY OF THE MARKETING MIX OF THE KUANTAN-II FRIED BANANA AGROINDUSTRY BUSINESS IN THE SUB-DISTRICT OF LIMA PULUH KOTA PEKANBARU USING AHP METHOD - Maisari, Astrie Vita; Nizar, Rini; Yasid, Hamdan (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
The purpose of this research is to analyze the priority of the right marketing mix decision in the fan-fried banana agro-industry Kuantan-II. The research method for drawing samples was carried out by using purposive sampling technique. The data analysis method to analyze the priority of the marketing mix uses the AHP (Analytical Hierarchy Process) method manually using Excel software.From the results of the priority research analysis of the Marketing Mix (Marketing Mix) in the Kuantan-II Fan Fried Banana agro-industry, it is known that: Producers or Business Actors of Kipas Kuantan-II Fried Banana must innovate because it produces the highest weight (0,522), the Marketing Mix that must be done Producers prioritize products with the highest weight (0,361), compared to Price with a weight (0,310), Promotion with a weight (0,166), and Distribution with a weight (0,161). The sub-mix on product variables that must be considered by producers or business actors is product quality with the highest weight (0,477). Business actors should innovate on their products, considering the increasingly fierce competition at this time. Innovations such as starting to penetrate into e-commerce will make the reach of consumers wider in the current era of digitalization. In addition, business actors must maintain the quality of their products so that consumers always trust and do not switch to similar competitors. In the promotion variable, business actors should promote their company without always involving other agencies. Although promotion is the third priority in the marketing mix variable, business actors must continue to carry out promotions because with the existence of